Prevalence and Risk Factors of Human Intestinal Parasites in Roudehen, Tehran Province, Iran - HEMMATI, Nasrin (Iran J Parasitol, 2017)
BACKGROUND: Intestinal parasitic infections are among the most common infections and health problems worldwide. Due to the lack of epidemiologic information of such infections, the prevalence of, and the risk factors for, enteric parasites were investigated in residents of Roudehen, Tehran Province, Iran. METHODS: In this cross-sectional study, 561 triple fecal samples were collected through a two-stage cluster-sampling protocol from Jun to Dec 2014. The samples were examined by formalin-ether concentration, culture, and with molecular methods. RESULTS: The prevalence of enteric parasites was 32.7% (95% CI 27.3–38). Blastocystis sp. was the most common intestinal protozoan (28.4%; 95% CI 23.7–33.0). The formalin-ether concentration and culture methods detected Blastocystis sp., Entamoeba coli, Giardia intestinalis, Dientamoeba fragilis, Iodamoeba butschlii, Entamoeba complex cysts or trophozoite, Chilomastix mesnilii, and Enterobius vermicularis. Single-round PCR assay for Entamoeba complex were identified Entamoeba dispar and E. moshkovskii. E. histolytica was not observed in any specimen. Multivariate analysis showed a significant association of parasites with water source and close animal contact. There was no correlation between infections and gender, age, occupation, education, or travel history. Protozoan infections were more common than helminth infections. CONCLUSION: This study revealed a high prevalence of enteric protozoan parasite infection among citizens of Rodehen. As most of the species detected are transmitted through a water-resistant cyst, public and individual education on personal hygiene should be considered to reduce transmission of intestinal parasites in the population.